The genus Aspilota Foerster (Hymenoptera: Braconidae: Alysiinae) in western Asia - Francisco Javier Peris Felipo; Ali Ameri; Ehsan Rakhshani; Sergey Belokobylskij (Journal of Insect Biodiversity and Systematics, 2016)
New data for the genus Aspilota Foerster, 1863 (Braconidae: Alysiinae) of the Western Asia are provided. Four species, A. flagimilis Fischer, 1966, A. insolita (Tobias, 1962), A. latitemporata Fischer, 1976 and A. nidicola Hedqvist, 1972, are recorded for the first time from Iran. Illustrated re-descriptions of Aspilota alfalfae Fischer, Lashkari Bod, Rakhshani & Talebi, 2011, A. delicata Fischer, 1973, A. flagimilis, A. insolita, A. latitemporata, and A. nidicola are presented. A key to the Western Asian species of Aspilota is provided.